Overview Of Knowledge Of English Language Education Students Class Of 2021 About Minimum Pairs - Nabila Yun Afifah; Riski Putri Yunnisa Khairani; Yani Lubis (Universitas Maritim AMNI Semarang, 2023)
The study of the English language's phonology, or sound system, is known as English phonology. To understand each other between speakers and listeners, English users must be able to pronounce correctly so that the message is conveyed without misunderstanding. One of the important points that must be learned from the science of phonology is minimal pair words to train English language learners to speak like native speakers. This descriptive study aims to determine the level of knowledge of students about the lecture material that has been studied in the fourth semester, namely Minimal Pairs. The study method is cross-sectional with a sample size of 126 respondents taken by consecutive sampling. The level of knowledge of students was found to be in the good category as much as 32.5%, sufficient category as much as 62.7%, poor category by 4.8%. Most of the respondents, 62.7%, had a sufficient level of knowledge. The conclusion obtained from this study is that students majoring in English tadris class of 2021 UIN North Sumatra have a sufficient level of knowledge about Minimal Pairs.